2020
DOI: 10.1101/2020.07.15.204545
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Varying perivascular astroglial endfoot dimensions along the vascular tree maintain perivascular-interstitial flux through the cortical mantle

Abstract: The glymphatic system is a recently defined brain-wide network of perivascular spaces along which cerebrospinal fluid (CSF) and interstitial solutes exchange. Astrocyte endfeet encircling the perivascular space form a physical barrier in between these two compartments, and fluid and solutes that are not taken up by astrocytes move out of the perivascular space through the junctions in between astrocyte endfeet. However, little is known about the anatomical structure and the physiological roles of the astrocyte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 66 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…2A-B; see Methods and C in SM). Note that prior studies ( 23, 28,36 ) suggest CSF from penetrating PVSs primarily enters the ECS via gaps between astrocyte endfeet. The upper and lower bounds that we set on the parenchymal permeability κ par come from two commonly cited studies ( 31,37 ); multiple other studies ( 3842 ) have reported κ par values within these bounds.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…2A-B; see Methods and C in SM). Note that prior studies ( 23, 28,36 ) suggest CSF from penetrating PVSs primarily enters the ECS via gaps between astrocyte endfeet. The upper and lower bounds that we set on the parenchymal permeability κ par come from two commonly cited studies ( 31,37 ); multiple other studies ( 3842 ) have reported κ par values within these bounds.…”
Section: Resultsmentioning
confidence: 90%
“…CSF leaves the perivascular space (green) surrounding penetrating arterioles (red) via gaps of width g and thickness T . The gaps between endfeet are long and narrow, as described by Wang et al ( 28 ). To estimate the hydraulic resistance of the gaps, we consider flow between infinite parallel plates.…”
Section: Movie Captionsmentioning
confidence: 88%
See 2 more Smart Citations
“…Indeed, Bork et al [14] recently proposed a mechanical model of flexible endfeet in which a fluctuating pressure causes the endfeet to flap in a way that promotes a directional flow, similar to the action of a bicuspid valve. Several studies using extracellular tracers indicate that fluid communication between PVSs and the ECS occurs mostly through the gaps between endfeet (see the reviews [1,15,16]). (It has also been suggested that some communication occurs through the astrocyte bodies themselves [17].)…”
Section: Introductionmentioning
confidence: 99%